On the political right, the customer is always right: Political ideology, entitlement, and complaining - Shepherd, Steven; Teymouri Athar, Hesam; Zaboli, Sahel (Journal of Consumer Psychology, 2024)
Across three preregistered studies and five supplementary datasets, we predicted and found that conservatives were more inclined to complain than liberals due to conservative consumers feeling a greater sense of entitlement. This research contributes to the literature by introducing consumer entitlement as a novel explanation for ideological differences in consumer behavior, and by building on previous work suggesting that conservative consumers complain less than liberals ( Journal of Consumer Research , 2017, 44 , 477). Evidence is provided across several service contexts and types of complaining behaviors. Study 1 and 4 supplementary datasets supported the basic process. Next, theory‐relevant boundary conditions provided converging process evidence. In Study 2, complaining intentions decreased among conservatives when they felt less (vs. more) entitled than the target of social comparison. In Study 3, complaining intentions decreased among conservatives when a service recovery was framed as providing special treatment. Implications and future research directions are discussed.